1991
DOI: 10.1073/pnas.88.11.4666
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane domain length variation in the evolution of major histocompatibility complex class I genes.

Abstract: The fifth exons of major histocompatibility complex (MHC) class I genes encode a transmembrane domain (TM) that is largely responsible for class I antigen cell-surface expression usually through conventional hydrophobic amino acid-membrane interactions or, less often, through phosphatidylinositol linkage. In this report we show that Peromyscus lucopus, a Cricetidae rodent, has MHC class I genes (Pele-A genes) encoding three distinct sizes of TMs. Increases in TM lengths were due to tandem duplications ofsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…some intragroup variation (group A) it is clear that this trait is not necessarily a good phylogenetic marker. Small variations in MHC class I gene TM length have been observed in other species, and it has been suggested that this area represents a hotspot for recombination and so is particularly susceptible to tandem duplications and deletions (Crew et al 1991), although we found no evidence of these processes here.…”
Section: Discussioncontrasting
confidence: 56%
“…some intragroup variation (group A) it is clear that this trait is not necessarily a good phylogenetic marker. Small variations in MHC class I gene TM length have been observed in other species, and it has been suggested that this area represents a hotspot for recombination and so is particularly susceptible to tandem duplications and deletions (Crew et al 1991), although we found no evidence of these processes here.…”
Section: Discussioncontrasting
confidence: 56%
“…The transmembrane domain of Ceat-B*1101 was unusual in that there was a three amino acid insertion of alanine, valine, valine (AVV) which appeared to be due to a tandem duplication (Figure 1). A nine base pair duplication in the transmembrane domain of MHC class I genes has been reported in chimpanzee B-locus alleles and rodent MHC class I genes (Mayer et al 1988, Crew et al 1991). It is noteworthy that the duplication (AVV) in the chimpanzee allele is similar to that observed in Ceat-B*1101 .…”
Section: Resultsmentioning
confidence: 99%
“…The transmembrane region amino acid sequence is significantly different among most class I genes of the rat , yet the deduced amino acid sequence of the transmembrane region of Eu was identical to that of K. In addition, the organization of the repeat in the transmembrane region of both genes is more like that of the mouse than that of other class I genes of the rat (Brorson et al 1989;Crew et al 1991;Rothermel et al 1993). From the evolutionary point of view, therefore, there may have been a duplication of a common ancestral gene that gave rise to RT1.K and RT1.E u, which in turn gave rise to the class I genes in the A region and in the E/C region, respectively, by duplication and subsequent mutation or segmental exchange.…”
Section: T G a C C T T G G A C T T G G A C T C T A T G C~t A T A~g mentioning
confidence: 90%